IDENTIFYING WORKPLACE STRESSORS IN THE EMERGENCY DEPARTMENT—AN EXPLORATORY STUDY. Issue 12 (23rd November 2015) - Basu, S; Yap, C; mason, S
Abstract : Objectives & Background: Stress amongst ED staff has been studied previously with observational research conducted since the 1980s. Many have measured outcomes of exposure to stress such as mental ill-health and more recently burnout. The factors which underlie workplace stress in the ED however are not well understood. This study aims to explore these issues in more detail. Methods: The HSE stress indicator tool was administered to all staff working in the ED at the Northern General Hospital in Sheffield in November 2014 (Doctors, Nurses, Support Workers, Admin, Orderlies and Domestics). Results were analysed using the HSE analysis tool which compared our results against 136 other surveyed organisations in the UK. Following the survey, six focus groups containing a mixture of professional groups were held in which results were presented, factors underpinning observed results were discussed and issues that were not identified in the questionnaire highlighted. A more detailed questionnaire was developed. Results: Overall response rate was 66%. All six staff groups identified high levels of demand and low levels of control over their work. Nursing staff displayed the highest levels of stress across the seven domains of the tool with little difference with respect to seniority of grade. Junior doctors displayed the lowest levels of stress of all professional groups. Higher levels of stress were seen in consultants than other medical grades. Orderlies and domestics whilst scoring higher on the demand/control domains, scored similarly to other groups with respect to support and relationships with colleagues (Table 1). Focus groups with staff identified issues relating to effort-reward imbalance and organisational justice which were not covered by the HSE tool. A more detailed questionnaire including these models of stress will be administered in July 2015 and to a control group from another hospital department which will be presented at the conference if the abstract is accepted. Conclusion: This exploratory study has identified differences in the origins and nature of workplace stressors affecting professional groups in our ED. If they are to be successful, interventions aimed at tackling workplace stress in the ED should take account of these differences. Further work should explore whether our results reflect those of other EDs and develop appropriately tailored intervention to address this issue on a wider scaleFigure 1 .